Pembuatan Survival Action Game Dengan Non-Player Character Berbasis Neural Network - Semuel Yootje Daniel Tawas; Gregorius Satia Budhi; Kristo Radion Purba (Jurnal Infra, 2016)
Game is a multi media application that need some main parts such as, goal, challenge and game play or usually has been know as rules in a game.Survival action game will apply real time system in its game play. Real time game usually needs fast decision making method for artificial intelligence, so it can’t interrupt any system in the game.Backpropagation is one of the fastest method that can be used to process data for decision making. Backpropagation method can use data training transformation feature so outputs from backpropagate calculation can be different than before. In its application, backpropagation needs to applying winner-take-all architecture so backpropagation system, can run the training process nicely.Based on testing result, backpropagation system can be applied in real time game and data training addition feature can gives the transformation for making decision that can be different than before.